Effects of core air gaps and steel inserts on thermal response of GFRP-balsa sandwich panels subjected to fire. (December 2022) - Vahedi, Niloufar; Correia, João R.; Vassilopoulos, Anastasios P.; Keller, Thomas
Abstract: Sandwich systems composed of combustible glass fiber-reinforced polymer (GFRP) face sheets and balsa cores must fulfill fire resistance requirements if used, for instance, in bridge or building construction. Air gaps and steel inserts in the balsa core, the latter to suspend external pipes below bridge decks for example, may therefore present critical zones where heat ingress is facilitated, and fire resistance is therefore reduced. The thermal responses of such GFRP-balsa sandwich panels comprising through-thickness air gaps or steel inserts, and subjected to a one-sided external fire, were thus investigated by furnace experiments and fluid-structure interaction simulations. Through-thickness air gaps and steel inserts between the face sheets cooled the surrounding zones close to the hot face and heated those located towards the cold face. In T-shape steel inserts penetrating the bottom face sheet, the fire-exposed flange collected the heat and the whole section around the insert was significantly heated. The results revealed that the remaining cross section might be considerably reduced by char formation around the air gaps and steel inserts. Although the effect is quite local, it may be significant if slabs are unidirectional or if it occurs at critical locations, e.g., in the vicinity of supports.